Railroad Ballast Testing and Properties 2018
DOI: 10.1520/stp160520170029
|View full text |Cite
|
Sign up to set email alerts
|

Two Decades of Advancement in Process Simulation Testing of Ballast Strength, Deformation, and Degradation

Abstract: This paper describes salient features of a set of large-scale ballast testing equipment developed at the University of Wollongong, Australia, and how the test results and research outcomes have contributed to transforming tracks in the Australian heavy haul and commuter networks, particularly with regards to the strength, deformation, and degradation of ballast. Ideally, ballast assemblies should be tested in prototype scale under actual loading conditions. This is because a reduction in particle sizes for tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…Railroads ensure the biggest network for quick and secure, public and freight transportation on rails over the world [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Railroads ensure the biggest network for quick and secure, public and freight transportation on rails over the world [1].…”
Section: Introductionmentioning
confidence: 99%
“…The most important roles of ballast materials are to distribute and reduce forces affecting sleepers, provide horizontal resistance, and ensure quick dewatering. Ballast for high loads and stability must be angular, well graded, and dense (i.e., well compacted), but this structure hinders drainage [1].…”
Section: Introductionmentioning
confidence: 99%
“…to enhance rail ballast performance and reduce its degradation [6][7][8][9][10][11][12]. Field trials by Indraratna et al [13] showed that rubber mats could significantly minimise ballast deformations, apart from reducing particle breakage. Previous laboratory studies using large-scale test facilities indicated that plastic under sleeper pads placed beneath sleepers could minimise ballast breakage by mitigating the transmission of impact loading effects [14].…”
Section: Introductionmentioning
confidence: 99%
“…placed at the interfaces between rails and sleepers); (ii) under sleeper pads (i.e. placed at the sleeper/ballast interfaces); (iii) rubber mats installed beneath the ballast (shock mats); and (iv) ballast mixed with rubber crumbs or shreds [17,41,60]. The inclusion of rubber shock mats decreases the hard interface between the ballast aggregates and other track components, such as the sleepers or underlying formations, and allows the particles bedding into softer pads, thus enhancing the area of contact of the aggregates and minimising the inter-particle contact forces [42,47,51].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of rubber shock mats decreases the hard interface between the ballast aggregates and other track components, such as the sleepers or underlying formations, and allows the particles bedding into softer pads, thus enhancing the area of contact of the aggregates and minimising the inter-particle contact forces [42,47,51]. Moreover, indirect methods to reduce the degradation of ballast by using rubber products in the sub-ballast layer have also been proposed in recent times, such as replacing the traditional sub-ballast with an energy-absorbing layer composed of waste materials, including coal wash, steel furnace slag and rubber crumbs [28,55], and using a capping layer confined with recycled rubber tyre cells [17]. In this paper, some of these methods involving the use of recycled rubber products in rail tracks will be presented and discussed.…”
Section: Introductionmentioning
confidence: 99%